Transverse bending behavior of the steel-UHPC lightweight composite deck: Orthogonal test and analysis. (November 2019) - Luo, Jun; Shao, Xudong; Cao, Junhui; Xiong, Manhua; Fan, Wei
Abstract: The lightweight composite deck (LWCD) is a new countermeasure to address issues of fatigue cracking in orthotropic steel decks (OSDs) and premature damage in asphalt overlays, which is composed of an OSD and a thin ultra-high performance concrete (UHPC) layer. The objective of this paper is to reveal the transversal bending behavior of the LWCD under negative bending moments. An orthogonal experimental test was accomplished on 40 steel-UHPC composite specimens. The specimens covered four parameters, i.e., the stud spacing, the UHPC thickness, the cover thickness, and the number of steel reinforcement in UHPC. The responses of the specimens were analyzed and discussed from different aspects, including the failure mode, the load-deflection curve, the strain distribution, the cracking status, and the interfacial slip. To facilitate the design of the LWCD, the influence of the four parameters on the average crack spacing, the cracking stress in UHPC and the ultimate load was discussed. In addition, equations for calculating the ultimate load of the composite specimens were proposed and were validated through the test results. Highlights: Influence of main design parameters on the transversal bending behavior is shown. Influence of main design parameters on the cracking stress is discussed. Influence of main design parameters on the ultimate load is discussed. Equations are developed to estimate the ultimate load of the steel-UHPC composite deck.